Six-Month Urinary CCL2 and CXCL10 Levels Predict Long-term Renal Allograft Outcome. Issue 9 (September 2016) - Hirt-Minkowski, Patricia; Rush, David N.; Gao, Ang; Hopfer, Helmut; Wiebe, Chris; Nickerson, Peter W.; Schaub, Stefan; Ho, Julie
Abstract : Background: Early prognostic markers that identify high-risk patients could lead to increased surveillance, personalized immunosuppression, and improved long-term outcomes. The goal of this study was to validate 6-month urinary chemokine ligand 2 (CCL2) as a noninvasive predictor of long-term outcomes and compare it with 6-month urinary CXCL10. Methods: A prospective, observational renal transplant cohort (n = 185; minimum, 5-year follow-up) was evaluated. The primary composite outcome included 1 or more: allograft loss, renal function decline (>20% decrease estimated glomerular filtration rate between 6 months and last follow-up), and biopsy-proven rejection after 6 months. CCL2/CXCL10 are reported in relation to urine creatinine (ng/mmol). Results: Fifty-two patients (52/185, 28%) reached the primary outcome at a median 6.0 years, and their urinary CCL2:Cr was significantly higher compared with patients with stable allograft function (median [interquartile range], 38.6 ng/mmol [19.7-72.5] vs 25.9 ng/mmol [16.1-45.8], P = 0.009). Low urinary CCL2:Cr (⩽70.0 ng/mmol) was associated with 88% 5-year event-free survival compared with 50% with high urinary CCL2:Cr ( P < 0.0001). In a multivariate Cox-regression model, the only independent predictors of the primary outcome were high CCL2:Cr (hazard ratio [HR], 2.86; 95% confidence interval [95% CI], 1.33-5.73) and CXCL10:Cr (HR, 2.35; 95% CI, 1.23-4.88; both P = 0.009). Urinary CCL2:Cr/CXCL10:Cr area under the curves were 0.62 ( P = 0.001)/0.63 ( P = 0.03), respectively. Time-to-endpoint analysis according to combined high or low urinary chemokines demonstrates that endpoint-free survival depends on the overall early chemokine burden. Conclusions: This study confirms that urinary CCL2:Cr is an independent predictor of long-term allograft outcomes. Urinary CCL2:Cr/CXCL10:Cr alone have similar prognostic performance, but when both are elevated, this suggests a worse prognosis. Therefore, urinary chemokines may be a useful tool for timely identification of high-risk patients. Abstract : In a prospective, observational renal transplant cohort with a follow-up of at least 5 years, the authors show that 6-month urinary CCL2:Cr is an independent predictor of long-term allograft outcomes. They confirm the same prediction value of 6-month urinaryCXCL10:Cr, the elevation of both biomarkers conveying an even worse prognosis. Supplemental digital content is available in the text.